Comparison of Children's Self-Reported and Parent-Reported Experiences of Food Insecurity and its Impact on School Motivation. - Vayisoglu, Sumbule Koksoy; Oncu, Emine (Journal of Child & Family Studies, 2025)
Food insecurity experience negatively impacts children's educational lives. Most studies assess children's food insecurity experience through parent reports. However, children may experience food insecurity differently, and this experience can affect their school motivation. This study aims to determine whether the parent-reported child's experience of food insecurity differs from the child's own reported experience. This study also examines the relationship between food insecurity experiences and socioeconomic status, and to evaluate the mediating roles of the child's health status, absenteeism, and perceived academic achievement in the relationship between both parent- and child-reported food insecurity experiences and school motivation. In a province in Turkey, 678 children aged 11–14 years and parents pairs from schools located in neighbourhoods with different socioeconomic levels were included in the study using a multi-stage stratified quota sampling method. Participants completed a self-administered questionnaire comprising various instruments. According to parental reports, food insecurity was experienced in four out of five households, while children's reports indicated that two out of every five experienced varying levels of food insecurity. Socioeconomic status was identified as the primary determinant of food insecurity, and discrepancies were found between parental and child reports. Child food insecurity experience was associated with school motivation through the mediating role of perceived academic achievement, while parental reports of food insecurity experience was associated with school motivation through the mediating role of perceived health status. Food insecurity experience was negatively associated with school motivation, potentially leading to issues with persistence in education. Early identification of at-risk children and families, and connecting them with community resources, can serve as a preventive measure. Highlights: Children's self-reported and parent-reported experiences of food insecurity differ. Socioeconomic status is a significant factor in determining both child and household food insecurity experiences. Children's food insecurity was negatively associated with school motivation indirectly through perceived academic achievement and parents' reports of food insecurity were negatively associated with school motivation indirectly through perceived health status. Identification of children and families at risk in schools and facilitating their access to community resources is essential.